Aqueous formaldehyde-free adhesive system, method for manufacturing a wood-based panel and wood-based panel
Patent Information
- Application Number
- CN202611100644.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]有鉴于此,本公开实施例致力于提供一种无醛胶黏剂体系、人造板制备方法及人造板,以解决现有技术中豆基胶黏剂耐水性差、储存期短、易霉变、干燥能耗大、固化胶层脆性大或工艺适配性不足的问题
[0014]在本公开的实施例中,通过防霉颗粒的核壳结构设计,利用壳层的亲水性官能团改善了疏水性防霉剂在含水的木质单元表面的水分散能力,避免了直接使用疏水性防霉剂时易出现的局部团聚和分布不均问题,确保了疏水性防霉剂的均匀分布和有效利用率。壳层在热压处理过程中发生物理变化(如软化、破裂等)以释放或暴露疏水性防霉剂,实现了防霉剂释放时机与热压固化过程的同步,提高了防霉效力的可控性和稳定性。壳层上的亲水性官能团能够与交联剂发生化学反应,使壳层组分共价键合至交联固化网络中,避免了非反应性壳层残留在交联固化网络中形成缺陷或削弱胶合强度,从而使无醛胶黏剂体系具有优异防霉性能的同时维持了其形成的交联固化网络的力学强度和耐水性。此外,豆基蛋白粉被配置为利用木质单元的水分在原位进行润胀和活化,无需预先制备水性胶液,省去了胶液储存、防霉、黏度控制及后续干燥等工序,降低了能耗和霉变风险。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of biomass formaldehyde-free adhesive technology, specifically to a formaldehyde-free adhesive system, a method for preparing engineered wood products, and engineered wood products. Background Technology
[0002] In the field of engineered wood products manufacturing, the use of biomass-based formaldehyde-free adhesives to replace traditional formaldehyde-containing adhesives has become an important technological development direction. Soy protein powder is favored due to its wide availability, renewability, and lack of formaldehyde release risk. However, its application in continuous production, particularly its direct mixing with wood units containing a certain amount of moisture, and the subsequent development of an adhesive system that combines water resistance, mildew resistance, and process adaptability, remains a goal the industry strives to achieve. Summary of the Invention
[0003] In view of this, the present disclosure aims to provide a formaldehyde-free adhesive system, a method for preparing engineered wood products, and engineered wood products, in order to solve the problems of poor water resistance, short shelf life, easy mold growth, high drying energy consumption, high brittleness of cured adhesive layer, or insufficient process adaptability of soybean-based adhesives in the prior art.
[0004] In a first aspect, embodiments of this disclosure provide a formaldehyde-free adhesive system, comprising: soy protein powder; a crosslinking agent; and anti-mold particles, the anti-mold particles comprising an anti-mold particle body and a shell layer, the shell layer covering at least a portion of the anti-mold particle body; the anti-mold particle body comprising a hydrophobic anti-mold agent; the shell layer comprising hydrophilic functional groups, wherein the shell layer is configured to undergo a physical change during hot pressing to release or expose the hydrophobic anti-mold agent, and the hydrophilic functional groups are capable of reacting with the crosslinking agent; wherein the soy protein powder is configured to swell and activate in situ using the moisture of the wood units.
[0005] In conjunction with the first aspect, in some embodiments, the crosslinking agent has a mass of 0.5% to 10% of the total mass of the formaldehyde-free adhesive system, and / or the anti-mold particles have a mass of 2% to 10% of the total mass of the formaldehyde-free adhesive system, and / or the anti-mold particles have a particle size of 50 nanometers to 100 micrometers.
[0006] In conjunction with the first aspect, in some embodiments, the above-described formaldehyde-free adhesive system further includes epoxidized natural rubber, wherein the mass of the epoxidized natural rubber is 5% to 30% of the total mass of the formaldehyde-free adhesive system.
[0007] In conjunction with the first aspect, in some embodiments, the shell layer is any one of a composite shell layer of carboxymethyl starch and polyvinyl alcohol, a composite shell layer of carboxymethyl cyclodextrin and oxidized starch, a composite shell layer of carboxymethyl cyclodextrin and chitosan, or a composite shell layer of carboxymethyl cyclodextrin and quaternized chitosan.
[0008] In conjunction with the first aspect, in some embodiments, the hydrophilic functional groups of the shell include at least one of the following: hydroxyl, carboxyl, carboxylate, hydroxypropyl, and amino groups.
[0009] In conjunction with the first aspect, in some embodiments, the anti-mildew particle body is selected from: glyceryl monolaurate; or a complex of glyceryl monolaurate with glycerol triglycidyl ether and / or epoxidized natural rubber.
[0010] In conjunction with the first aspect, in some embodiments, the shell thickness is from 10 nanometers to 100 micrometers, and / or the crosslinking agent includes a polyepoxy crosslinking agent, which includes glycerol triglycidyl ether, and / or the physical changes include at least one of the following: softening, melting, cracking, and shrinkage.
[0011] Secondly, embodiments of this disclosure provide a method for preparing a wood-based panel, comprising: mixing soy protein powder, a crosslinking agent, and anti-mold particles with wood units to obtain a mixture, wherein the anti-mold particles include an anti-mold particle body and a shell layer, the shell layer covering at least a portion of the anti-mold particle body, the anti-mold particle body including a hydrophobic anti-mold agent; the shell layer including hydrophilic functional groups, the shell layer being configured to undergo physical changes during hot pressing to release or expose the hydrophobic anti-mold agent, and the hydrophilic functional groups being capable of reacting with the crosslinking agent; hot pressing the mixture, such that the soy protein powder swells and activates in situ using the moisture of the wood units, crosslinks and cures with the crosslinking agent, the shell layer undergoes physical changes during hot pressing to release or expose the hydrophobic anti-mold agent, and the hydrophilic functional groups react with the crosslinking agent to bond to the crosslinked and cured network.
[0012] In conjunction with the first aspect, in some embodiments, the wood unit includes at least one of the following: wood shavings, wood fibers, bamboo shavings, and bamboo fibers; and / or, the moisture content of the wood unit is greater than 10%.
[0013] Thirdly, embodiments of this disclosure provide a wood-based panel, comprising: a plurality of wood units; and a cross-linked curing network cured between the wood units, the cross-linked curing network being formed by curing the aforementioned formaldehyde-free adhesive system after hot pressing.
[0014] In the embodiments of this disclosure, the core-shell structure design of the anti-mold particles utilizes the hydrophilic functional groups of the shell layer to improve the water dispersibility of the hydrophobic anti-mold agent on the surface of water-containing wood units. This avoids the local agglomeration and uneven distribution problems that easily occur when directly using hydrophobic anti-mold agents, ensuring the uniform distribution and effective utilization rate of the hydrophobic anti-mold agent. During the hot-pressing process, the shell layer undergoes physical changes (such as softening and cracking) to release or expose the hydrophobic anti-mold agent, achieving synchronization between the release timing of the anti-mold agent and the hot-pressing curing process, thus improving the controllability and stability of the anti-mold efficacy. The hydrophilic functional groups on the shell layer can chemically react with the crosslinking agent, causing the shell layer components to covalently bond to the crosslinked curing network. This avoids non-reactive shell layer residues in the crosslinked curing network forming defects or weakening the bonding strength, thereby enabling the formaldehyde-free adhesive system to maintain excellent anti-mold performance while preserving the mechanical strength and water resistance of the formed crosslinked curing network. In addition, the soy protein powder is formulated to utilize the moisture of the wood units for in-situ swelling and activation, eliminating the need for pre-preparation of water-based adhesives. This saves on processes such as adhesive storage, mold prevention, viscosity control, and subsequent drying, reducing energy consumption and the risk of mold growth. Attached Figure Description
[0015] Figure 1 The diagram shown is a schematic diagram of the framework of a formaldehyde-free adhesive system provided in an embodiment of this disclosure.
[0016] Figure 2 The diagram shown is a flowchart illustrating a method for preparing a wood-based panel according to an embodiment of this disclosure. Detailed Implementation
[0017] The technical solutions of the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments of this disclosure, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this disclosure.
[0018] Furthermore, to better illustrate this disclosure, numerous specific details are set forth in the following detailed description. Those skilled in the art will understand that this disclosure can be practiced without certain specific details. In some instances, methods and means well-known to those skilled in the art have not been described in detail in order to highlight the main points of this disclosure.
[0019] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0020] In related technologies, adhesives typically need to be pre-prepared into water-based solutions or slurries. This involves dispersing soy protein powder in water and subjecting it to alkalization or modification before applying it to the surface of the wood unit. Wet adhesive solutions often suffer from problems such as short shelf life, susceptibility to mold growth, continuous viscosity increases, and increased energy consumption during subsequent drying. To impart anti-mold properties to bonded products, hydrophobic long-chain antifungal agents such as glyceryl monolaurate possess broad-spectrum antibacterial activity. However, due to their poor water solubility, when directly mixed into soy protein powder and wood units in powder form, localized aggregation easily occurs, resulting in uneven distribution of the antifungal agent, reduced effective utilization, and even potential disruption of the bonding interface continuity.
[0021] To address the aforementioned technical problems, this disclosure provides a formaldehyde-free adhesive system comprising: soy protein powder; a crosslinking agent; and anti-mold particles. The anti-mold particles include an anti-mold particle body and a shell layer, the shell layer coating at least a portion of the anti-mold particle body. The anti-mold particle body includes a hydrophobic anti-mold agent; the shell layer includes hydrophilic functional groups. The shell layer is configured to undergo a physical change during hot-pressing to release or expose the hydrophobic anti-mold agent, and the hydrophilic functional groups are capable of reacting with the crosslinking agent. The soy protein powder is configured to swell and activate in situ using the moisture in the wood unit. Thus, through the core-shell structure design of the anti-mold particles, the hydrophilic functional groups of the shell layer improve the water dispersibility of the hydrophobic anti-mold agent on the surface of the water-containing wood unit, avoiding the localized agglomeration and uneven distribution problems that easily occur when directly using hydrophobic anti-mold agents, ensuring the uniform distribution and effective utilization of the hydrophobic anti-mold agent. During hot-pressing, the shell undergoes physical changes (such as softening and cracking) to release or expose the hydrophobic antifungal agent, synchronizing the release of the antifungal agent with the hot-pressing curing process, thus improving the controllability and stability of the antifungal efficacy. The hydrophilic functional groups on the shell can chemically react with the crosslinking agent, covalently bonding the shell components to the crosslinked curing network. This avoids non-reactive shell residues forming defects or weakening the bond strength within the crosslinked curing network, thereby ensuring that the formaldehyde-free adhesive system maintains excellent antifungal properties while preserving the mechanical strength and water resistance of the formed crosslinked curing network. Furthermore, the soy protein powder is formulated to utilize the moisture in the wood units for in-situ swelling and activation, eliminating the need for pre-prepared water-based adhesive solutions. This eliminates the need for adhesive storage, antifungal treatment, viscosity control, and subsequent drying processes, reducing energy consumption and the risk of mold growth.
[0022] The following is based on Figure 1 The formaldehyde-free adhesive system disclosed herein is described in detail.
[0023] Figure 1 The diagram shown is a schematic diagram of the framework of a formaldehyde-free adhesive system provided in an embodiment of this disclosure.
[0024] like Figure 1As shown, the formaldehyde-free adhesive system 100 includes: soy protein powder 110, crosslinking agent 120, and anti-mold particles 130, wherein the anti-mold particles 130 may include an anti-mold particle body and a shell layer, and the shell layer covers at least part of the anti-mold particle body.
[0025] For example, the anti-mold granule body includes a hydrophobic anti-mold agent; the shell includes hydrophilic functional groups, wherein the shell is configured to undergo physical changes during hot pressing to release or expose the hydrophobic anti-mold agent, and the hydrophilic functional groups are capable of reacting with a crosslinking agent; the soy protein powder is configured to swell and activate in situ (on the surface of the wood unit) using the moisture of the wood unit.
[0026] For example, soy protein powder 110 can characterize protein materials derived from legumes and existing in powder form. Examples include, but are not limited to: defatted soy flour, soy protein concentrate, soy protein isolate, soy protein powder, or combinations thereof. For example, swelling and activation can characterize the process by which soy protein powder 110, upon contact with hydrated lignin units, absorbs moisture from the lignin units, causing the protein particles to expand in volume and stretch in structure.
[0027] In some embodiments, soy protein powder 110 can be directly mixed with wood units in dry powder form without prior dispersion and modification in water to prepare an aqueous adhesive. Soy protein powder 110 can be configured to swell and activate upon contact with water-containing wood units using the wood units' own moisture content; that is, using the moisture contained within the wood units as an in-situ activation water source, allowing the soy protein powder 110 to complete swelling and activation during stirring and hot pressing. Using soy protein powder 110 in dry powder form eliminates the step of pre-preparing an aqueous adhesive, avoiding common problems in aqueous adhesive systems such as short shelf life, viscosity increase, susceptibility to mold, and transportation difficulties. Furthermore, by utilizing the moisture contained within the wood units as an activation water source, soy protein powder 110 can complete swelling and activation in situ (on the surface of the wood units) without the need for adding large amounts of additional water, simplifying the process, reducing drying energy consumption, and allowing the activation process to be carried out simultaneously with sizing and hot pressing, thus improving production efficiency.
[0028] Exemplarily, the anti-mold particles 130 can be characterized as microparticles having a core-shell structure. In some embodiments, the anti-mold particles 130 comprise at least one anti-mold particle body (or core) primarily composed of a hydrophobic anti-mold agent, and a shell layer covering at least a portion of the anti-mold particle body, the shell layer containing hydrophilic functional groups. The hydrophobic anti-mold agent can be characterized as a compound or mixture having hydrophobic properties and capable of inhibiting or delaying mold growth. For example, the hydrophobic anti-mold agent can be glyceryl monolaurate. Exemplarily, physical changes can be characterized as a physical morphological transformation of the shell layer due to temperature during hot pressing, which allows the hydrophobic anti-mold agent to be released, thus exposing the hydrophobic anti-mold agent. Exemplarily, the hydrophilic functional group can be characterized as a chemical group capable of forming hydrogen bonds or ion hydration with water molecules to impart hydrophilic dispersibility to the shell layer, and the hydrophilic functional group is capable of reacting with a crosslinking agent.
[0029] For example, the anti-mold granules 130 may include granules in the form of microcapsules or microspheres. The core-shell structure allows the hydrophobic anti-mold agent to be coated by a shell containing hydrophilic functional groups. The hydrophilic functional groups can improve the dispersibility of the anti-mold granules in water-containing wood units, avoid local agglomeration when the hydrophobic anti-mold agent is added directly in powder form, and improve the uniformity of the distribution of the hydrophobic anti-mold agent. They can also achieve controlled release of the hydrophobic anti-mold agent through physical changes during hot pressing, thereby improving the effective utilization rate of the anti-mold agent.
[0030] In some embodiments, the hydrophobic antifungal agent can be a fatty acid ester antifungal agent with a hydrophobic long chain, such as glyceryl monolaurate, or other antibacterial and antifungal active substances with hydrophobic properties. The hydrophobic antifungal agent possesses both hydrophobic long chains and antibacterial and antifungal potential, and after thermo-pressurization, it can be effectively distributed within the cross-linked cured network to exert a long-lasting antifungal effect.
[0031] In some embodiments, the shell is configured to undergo physical changes during hot-pressing to release or expose the hydrophobic antifungal agent. Specifically, the shell undergoes structural changes under hot-pressing conditions (exposed to temperature and / or pressure), causing the encapsulated hydrophobic antifungal agent to be released or partially exposed. The thermal response characteristics of the shell synchronize the release of the hydrophobic antifungal agent with the hot-pressing process, improving the utilization efficiency of the hydrophobic antifungal agent and the uniformity of the antifungal effect.
[0032] Exemplarily, crosslinking agent 120 can be a compound capable of chemically reacting (e.g., epoxy ring-opening reaction) with the hydrophilic functional groups in the shell of soybean protein powder 110 and / or anti-mildew granules 130, thereby promoting the formation of a crosslinked curing network. For example, it may include, but is not limited to, polyepoxy crosslinking agents such as glycerol triglycidyl ether, ethylene glycol diglycidyl ether, triglycidylamine, etc. In some embodiments, crosslinking agent 120 is used for crosslinking curing during hot pressing, jointly constructing a crosslinked curing network with the hydrophilic functional groups of soybean protein powder 110 and the shell, thereby improving the water resistance and mechanical strength of the crosslinked curing network. Exemplarily, the crosslinked curing network can be a three-dimensional polymer network structure formed by hot pressing and curing soybean protein powder 110, crosslinking agent 120, and the reacting shell and / or other reactive components (such as epoxidized natural rubber), which is used to bond and connect wood units together.
[0033] In some embodiments, the hydrophilic functional groups of the shell can react with the crosslinking agent 120. Specifically, the shell, through its hydrophilic functional groups (such as hydroxyl groups), can chemically react with the epoxy groups of the crosslinking agent 120 (e.g., ring-opening reaction) to form covalent bonds such as ether bonds, thus covalently bonding the shell to the crosslinked curing network. In other embodiments, if the soy protein powder 110 contains hydrophilic groups, these groups can chemically react with the hydrophilic groups of the shell (such as hydroxyl, amino, and carboxyl groups) to form covalent bonds such as hydrogen bonds, thus hydrogen-bonding the shell to the crosslinked curing network. The shell reacts with the crosslinking agent and soy protein powder through its hydrophilic functional groups, covalently bonding and hydrogen-bonding to the crosslinked curing network, or becoming part of the crosslinked curing network. This avoids the problem of shell residues existing as non-reactive foreign matter in the crosslinked curing network and weakening the bonding strength, thereby maintaining or even improving the mechanical properties and water resistance of the crosslinked curing network while achieving anti-mildew function.
[0034] By designing the core-shell structure of the anti-mold particles, the hydrophilic functional groups of the shell layer improve the water dispersibility of the hydrophobic anti-mold agent on the surface of water-containing wood units, avoiding the local agglomeration and uneven distribution problems that easily occur when directly applying hydrophobic anti-mold agents, thus ensuring the uniform distribution and effective utilization rate of the hydrophobic anti-mold agent. During the hot-pressing process, the shell layer undergoes physical changes (such as softening and cracking) to release or expose the hydrophobic anti-mold agent, achieving synchronization between the release timing and the hot-pressing curing process, improving the controllability and stability of the anti-mold efficacy. The hydrophilic functional groups on the shell layer can chemically react with the crosslinking agent, causing the shell layer components to covalently bond to the crosslinked curing network. This avoids non-reactive shell layer residues in the crosslinked curing network forming defects or weakening the adhesive strength, thus enabling the formaldehyde-free adhesive system to maintain excellent anti-mold performance while preserving the mechanical strength and water resistance of the formed crosslinked curing network. In addition, the soy protein powder is formulated to utilize the moisture of the wood units for in-situ swelling and activation, eliminating the need for pre-preparation of water-based adhesives. This saves on processes such as adhesive storage, mold prevention, viscosity control, and subsequent drying, reducing energy consumption and the risk of mold growth.
[0035] In some embodiments, the crosslinking agent is 0.5% to 10% of the total mass of the formaldehyde-free adhesive system, and / or the anti-mold particles are 2% to 10% of the total mass of the formaldehyde-free adhesive system, and / or the particle size of the anti-mold particles is 50 nanometers to 100 micrometers.
[0036] In some embodiments, the mass of the crosslinking agent can range from 0.5% to 10% of the total mass of the formaldehyde-free adhesive system. A crosslinking density below 0.5% may be insufficient to provide the required water resistance and mechanical strength, while a crosslinking agent above 10% may lead to over-rigidification of the crosslinked network or increased cost; this range (0.5% to 10%) helps to achieve a reasonable balance between crosslinking density, crosslinked network flexibility, and cost.
[0037] In some embodiments, the mass of the anti-mold particles can be between 2% and 10% of the total mass of the formaldehyde-free adhesive system. When the mass of the anti-mold particles is less than 2%, the effective concentration of the hydrophobic anti-mold agent may not be sufficient to provide adequate anti-mold protection. When the mass of the anti-mold particles is greater than 10%, the excessive amount of hydrophobic anti-mold particles may affect the continuity of the cross-linked curing network and the bonding strength. This range (2% to 10%) helps to achieve a balance between anti-mold effect and bonding performance.
[0038] In some embodiments, the particle size of the anti-mold particles can be in the range of 50 nanometers to 100 micrometers. If the particle size of the anti-mold particles is too large, the dispersion uniformity of the anti-mold particles on the surface of the wood unit may decrease. If the particle size of the anti-mold particles is too small, the particle preparation difficulty and cost may increase and secondary agglomeration may easily occur. This range (50 nanometers to 100 micrometers) helps to balance the dispersibility, thermal response release efficiency and manufacturability of the anti-mold particles.
[0039] By controlling the dosage range of the crosslinking agent, sufficient crosslinking density is ensured between the hydrophilic functional groups of the soy protein powder and the shell to form a dense crosslinked curing network, while avoiding the problems of excessive crosslinking agent leading to over-rigidification, increased brittleness, or increased costs in the crosslinked curing network. By limiting the dosage range of the anti-mold particles, the effective concentration of the hydrophobic anti-mold agent is ensured to provide sufficient anti-mold protection, while preventing excessive anti-mold particles from forming inclusions in the crosslinked curing network, thus disrupting continuity or reducing adhesive strength. By limiting the particle size range of the anti-mold particles, good uniform dispersion of the anti-mold particles on the surface of the water-containing wood unit is ensured, while ensuring that the shell can be opened in time during the hot pressing process, allowing the hydrophobic anti-mold agent to be effectively released. The synergistic limitation of the above three parameters achieves a balance between crosslinking curing effect, anti-mold efficacy, and process operability in the formaldehyde-free adhesive system.
[0040] In some embodiments, the formaldehyde-free adhesive system described above further includes epoxidized natural rubber, wherein the mass of the epoxidized natural rubber is 5% to 30% of the total mass of the formaldehyde-free adhesive system.
[0041] For example, epoxidized natural rubber can characterize an elastomer containing epoxy groups obtained by epoxidation modification of natural rubber, which can participate as a toughening component in the crosslinking and curing of formaldehyde-free adhesive systems. In some embodiments, the mass of epoxidized natural rubber can be 5% to 30% of the total mass of the formaldehyde-free adhesive system. When the mass of epoxidized natural rubber is less than 5%, the toughening effect may not be significant, and when the mass of epoxidized natural rubber is more than 30%, it may excessively reduce the modulus and stiffness of the crosslinked cured network; this range (5% to 30%) helps to achieve a balance between improving the toughness of the crosslinked cured network and maintaining its mechanical strength, thus achieving a synergistic effect of water resistance, mildew resistance, and toughening.
[0042] By synergistically combining epoxidized natural rubber as a toughening component with crosslinking agents and other components, the toughness of the crosslinked curing network is enhanced and its brittleness is reduced, thereby improving the impact resistance and durability of engineered wood panels prepared based on formaldehyde-free adhesive systems during use.
[0043] As explained above, the shell layer includes hydrophilic functional groups and can react with crosslinking agents. The following section further describes the material composition of the shell layer. The shell layer can be a composite shell made of natural polysaccharide-based materials containing hydrophilic functional groups, to balance water dispersibility, cost control, thermal responsiveness, and reactivity with crosslinking agents (such as glycerol triglycidyl ether).
[0044] In some embodiments, the shell is any one of a composite shell of carboxymethyl starch and polyvinyl alcohol, a composite shell of carboxymethyl cyclodextrin and oxidized starch, a composite shell of carboxymethyl cyclodextrin and chitosan, or a composite shell of carboxymethyl cyclodextrin and quaternized chitosan.
[0045] In one embodiment, the shell can be a composite shell of carboxymethyl starch and polyvinyl alcohol. Carboxymethyl starch provides hydrophilic groups such as carboxyl and carboxylate groups, while polyvinyl alcohol provides abundant hydroxyl groups and good film-forming properties. The shell formed by the composite of the two has good water dispersibility and thermal response characteristics. During hot pressing, the low softening point of PVA helps the shell to open. In addition, both carboxyl and hydroxyl groups can undergo ring-opening reactions with crosslinking agents, allowing the shell to participate in the construction of the crosslinked curing network.
[0046] In another embodiment, the shell can be a composite shell of carboxymethyl cyclodextrin and oxidized starch. Carboxymethyl cyclodextrin has a cavity structure and carboxyl functional groups, which helps to contain the hydrophobic antifungal agent and disperse it in an aqueous environment; oxidized starch contains aldehyde and carboxyl groups, providing active sites for reaction with crosslinking agents; the composite of the two has both water dispersibility and reactivity with glycerol triglycidyl ether, and the raw materials are widely available and low in cost.
[0047] In another embodiment, the shell can be a composite shell of carboxymethyl cyclodextrin and chitosan. Chitosan itself has certain antibacterial and antifungal activities and film-forming properties. The shell formed after being combined with carboxymethyl cyclodextrin not only provides water dispersibility, but also participates in cross-linking reactions through the amino groups of chitosan, and additionally imparts the antifungal particles with the antibacterial auxiliary effect of chitosan itself.
[0048] In another embodiment, the shell can be a composite shell of carboxymethyl cyclodextrin and quaternized chitosan. Compared with chitosan, quaternized chitosan has a stronger positive charge density and water solubility. The shell formed after being combined with carboxymethyl cyclodextrin has better water dispersibility, and the quaternary ammonium salt group itself has broad-spectrum antibacterial properties, which can synergistically enhance the overall antifungal effect with hydrophobic antifungal agents.
[0049] The shell materials (carboxymethyl starch, polyvinyl alcohol, carboxymethyl cyclodextrin, oxidized starch, chitosan, and quaternized chitosan) are all natural polymers or their modified products. The raw materials are widely available and cost-effective, and all contain abundant hydrophilic functional groups (such as hydroxyl, carboxyl, and amino groups), which endow the anti-mold particles with excellent water dispersibility on the surface of water-containing wood units. During hot pressing, these composite shells can reliably open through physical changes such as softening and melting, releasing the internal hydrophobic anti-mold agent. Furthermore, the active functional groups (such as hydroxyl, carboxyl, and amino groups) in these shell materials can undergo ring-opening reactions with the crosslinking agent, covalently bonding the shell to the crosslinked curing network and preventing it from weakening the strength of the crosslinked curing network as an inert inclusion.
[0050] As mentioned above, the shell includes hydrophilic functional groups. Further, in some embodiments, the hydrophilic functional groups of the shell include at least one of the following: hydroxyl, carboxyl, carboxylate, hydroxypropyl, and amino groups.
[0051] In some embodiments, hydroxyl groups are widely present functional groups in polysaccharide shell materials, capable of undergoing ring-opening reactions with crosslinking agents to form ether bonds, thus covalently bonding the shell to the crosslinking network. Furthermore, the hydrophilicity of hydroxyl groups facilitates the wetting and dispersion of the shell in aqueous environments. Carboxyl groups possess strong hydrophilicity and reactivity, capable of undergoing ring-opening esterification reactions with crosslinking agents to form ester bonds that connect to the crosslinking network. Moreover, the dissociation of carboxyl groups can enhance the electrostatic stability of the shell within aqueous lignin units.
[0052] In some embodiments, carboxyl groups (such as sodium carboxymethyl salt in carboxymethyl starch or carboxymethyl cyclodextrin) possess ionic hydrophilicity, providing stronger electrostatic dispersion stability in aqueous environments and contributing to the uniform distribution of anti-mold particles within water-containing wood units. Hydroxypropyl groups possess both hydrophilicity and a certain degree of steric hindrance, contributing to the flexibility and water solubility of the shell. Furthermore, the hydroxyl groups in hydroxypropyl groups can participate in ring-opening reactions with crosslinking agents. Amino groups (such as primary amino groups in chitosan or quaternized chitosan) can undergo ring-opening amination reactions with crosslinking agents to form secondary amine linkages; the reaction rate is relatively fast, helping to accelerate the bonding process of the shell to the crosslinked and cured network.
[0053] The hydrophilic functional groups (hydroxyl, carboxyl, carboxyl, hydroxypropyl, and amino) of the shell are key to giving the shell water dispersibility. They can form hydrogen bonds or ion-dipole interactions with water molecules in soy protein powder, ensuring that the anti-mold particles do not agglomerate in a humid environment. In addition, the hydrophilic functional groups of the shell can all undergo ring-opening reactions with cross-linking agents to form stable covalent bonds (such as ether bonds, ester bonds, and secondary amine bonds), firmly anchoring the shell to the cross-linked curing network.
[0054] The material composition and hydrophilic functional group types of the shell have been explained above. The composition scheme of the anti-mildew particle body (or core) will be further explained below. Depending on different performance requirements, the core can be made of a single material or a composite material.
[0055] In some embodiments, the anti-mildew particle body is selected from: glyceryl monolaurate; or a complex of glyceryl monolaurate with glycerol triglycidyl ether and / or epoxidized natural rubber.
[0056] As one embodiment, the anti-mold granules can be made from a single material: glyceryl monolaurate. The hydrophobic long-chain structure of glyceryl monolaurate can be directly distributed within the cross-linked curing network after thermo-pressurization, exerting its antibacterial and anti-mold effects, making it suitable for applications requiring basic anti-mold performance.
[0057] In another embodiment, the anti-mold particle body can be a complex of glyceryl monolaurate and glycerol triglycidyl ether. Glycerol triglycidyl ether can improve the dispersibility of glyceryl monolaurate in the anti-mold particle body. In addition, glycerol triglycidyl ether is a polyepoxy crosslinking agent, which can participate in the crosslinking and curing reaction nearby after hot-pressing release, so that the anti-mold particle body has both anti-mold and crosslinking functions, which helps to form a locally enhanced crosslinking network at the release site of the anti-mold agent.
[0058] In another embodiment, the antifungal particle body can be a composite of glyceryl monolaurate and epoxidized natural rubber. The flexible segments of the epoxidized natural rubber participate in cross-linking and curing after hot-pressing, which helps to achieve both antifungal and localized toughening effects at the antifungal agent release site, reducing the brittleness of the cross-linked cured network at that location.
[0059] In another embodiment, the anti-mold particle body can also be a composite of glyceryl monolaurate, glycerol triglycidyl ether, and epoxidized natural rubber, namely a ternary composite material of glyceryl monolaurate / glycerol triglycidyl ether / epoxidized natural rubber. This ternary composite material combines the anti-mold properties of glyceryl monolaurate, the cross-linking function of glycerol triglycidyl ether, and the toughening effect of epoxidized natural rubber. After hot-pressing release, the three components work synergistically in the same interface region, helping to achieve a comprehensive balance between anti-mold, cross-linking reinforcement, and toughening.
[0060] When the antifungal particles are made of composite material formed by glyceryl monolaurate, glycerol triglycidyl ether, and / or epoxidized natural rubber, the glycerol triglycidyl ether or epoxidized natural rubber can participate in the cross-linking and curing reaction nearby after the shell is opened. This enhances the network structure at the release sites of the hydrophobic antifungal agent, helps to regulate the release rate of the hydrophobic antifungal agent, promotes its diffusion, and achieves a synergistic effect of multiple components.
[0061] The above text has explained that the shell undergoes physical changes during hot pressing to release or expose the hydrophobic antifungal agent. The following text further explains the thickness parameters of the shell, the type of crosslinking agent, and the manner of physical changes.
[0062] In some embodiments, the shell thickness is from 10 nanometers to 100 micrometers, and / or the crosslinking agent includes a polyepoxy crosslinking agent, which includes glycerol triglycidyl ether, and / or the physical changes include at least one of the following: softening, melting, cracking, and shrinkage.
[0063] In some embodiments, the thickness of the shell layer can be in the range of 10 nanometers to 100 micrometers. Controlling the shell layer thickness within this range is crucial. If the shell layer is too thin, the shell layer's coverage of the anti-mold particles is insufficient, potentially leading to premature rupture and premature release of the hydrophobic anti-mold agent. If the shell layer is too thick, it may not fully open during hot pressing, affecting the release efficiency of the hydrophobic anti-mold agent. This range (of the shell layer) helps to achieve a balance between coverage stability and thermal response opening efficiency.
[0064] In some embodiments, the crosslinking agent may include a polyepoxy crosslinking agent. The polyepoxy crosslinking agent contains multiple epoxy groups, enabling it to simultaneously crosslink at multiple points with the active groups (such as amino and carboxyl groups) in the soy protein powder and the hydrophilic functional groups (such as hydroxyl, carboxyl, and amino groups) in the shell layer, forming a high-density crosslinked cured network, thereby improving the water resistance and mechanical strength of the crosslinked cured network. In some embodiments, the active groups (such as amino and carboxyl groups) in the soy protein powder may be obtained by alkalizing the soy protein powder with an alkaline solution. For example, the mass of the alkaline solution may be 1% to 50% of the total mass of the formaldehyde-free adhesive.
[0065] In some embodiments, the crosslinking agent may include glycerol triglycidyl ether. Glycerol triglycidyl ether is a multifunctional epoxy crosslinking agent, consisting of a single glycerol molecule with three glycidyl groups introduced through etherification, exhibiting high crosslinking efficiency. The ether bonds and epoxy groups in its molecular structure give it a certain degree of compatibility when combined with soy protein powder containing active groups (such as amino and carboxyl groups) and shells containing hydrophilic functional groups.
[0066] In some embodiments, the physical changes that occur in the shell during hot pressing may include at least one of the following: softening, melting, cracking, and shrinkage. Softening is a gradual opening mechanism that helps the hydrophobic antifungal agent to be released gradually rather than all at once during hot pressing, thereby achieving a more uniform distribution of the hydrophobic antifungal agent in the cross-linked curing network. In one embodiment, when the shell softens at the hot pressing temperature, the shell structure gradually relaxes, allowing the hydrophobic antifungal agent to penetrate, release, or be exposed. Melting allows the hydrophobic antifungal agent to be released rapidly and fully into the cross-linked curing network, suitable for process conditions requiring rapid and comprehensive distribution of the antifungal agent during hot pressing. In one embodiment, when the shell melts at the hot pressing temperature, the shell structure completely loses its encapsulation morphology, and the hydrophobic antifungal agent is fully released. Cracking can occur under specific temperature and pressure conditions during hot pressing, allowing the hydrophobic antifungal agent to be released in a concentrated manner when specific hot pressing conditions are reached, helping to match the release timing of the hydrophobic antifungal agent with the hot pressing curing process. When the shell layer cracks during hot pressing due to internal pressure differences or material embrittlement, the hydrophobic antifungal agent is released from the crack. Dehydration shrinkage is a common response behavior of natural polysaccharide shell materials in hot pressing environments. The antifungal agent is gradually released through the cracks or extrusion effect generated by shrinkage, which helps to ensure the gradual release and uniform distribution of the antifungal agent. In one embodiment, when the shell layer shrinks in volume due to dehydration or other reasons during hot pressing, cracks are generated in the shell layer or it contracts and squeezes out the hydrophobic antifungal agent, thereby achieving the release or exposure of the hydrophobic antifungal agent.
[0067] By limiting the thickness of the shell, sufficient integrity is ensured to cover the anti-mold granules without being too thick to hinder opening during hot pressing. The use of a multi-epoxy crosslinking agent ensures efficient multi-point crosslinking with the soy protein powder and the hydrophilic functional groups contained in the shell, forming a high-density crosslinked curing network. The specific limitation of physical changes makes the response behavior of the shell under hot pressing temperature and pressure clearly controllable (for example, by adjusting the shell composition, a gradual release mainly characterized by softening or a concentrated release mainly characterized by rupture can be achieved), providing a basis for adapting to different hot pressing process parameters.
[0068] The components and their synergistic mechanism of the formaldehyde-free adhesive system have been explained above. The method for preparing engineered wood panels using the above-mentioned formaldehyde-free adhesive system will be explained below.
[0069] The following is based on Figure 2 The method for preparing engineered wood panels using the above-described formaldehyde-free adhesive system, as provided in this disclosure, is described in detail.
[0070] Figure 2 The diagram shown is a schematic flow chart of a method for preparing a wood-based panel according to an embodiment of this disclosure. Figure 2 As shown, the method for preparing the artificial board provided in this embodiment may include the following steps.
[0071] Step S210: Mix soybean protein powder, crosslinking agent and anti-mold granules with wood unit to obtain mixture material.
[0072] For example, the anti-mold particles may include an anti-mold particle body and a shell layer, the shell layer covering at least a portion of the anti-mold particle body, the anti-mold particle body including a hydrophobic anti-mold agent; the shell layer including hydrophilic functional groups, the shell layer being configured to undergo physical changes during hot pressing to release or expose the hydrophobic anti-mold agent, and the hydrophilic functional groups being capable of reacting with a crosslinking agent.
[0073] In some embodiments, the wood-based unit can be the basic structural unit in the preparation of engineered wood products. The wood-based unit can be, for example, plant fiber-based materials such as wood shavings, wood fibers, bamboo shavings, or bamboo fibers. As the skeletal structure of the engineered wood product, the moisture contained within the wood-based unit can serve as a source of water for the in-situ swelling and activation of the soy protein powder, eliminating the need for adding large amounts of additional water during the preparation process.
[0074] For example, soy protein powder can be treated with an alkali solution to expose active groups (such as amino and carboxyl groups) in the soy protein powder. For example, the mass of the alkali solution can be 1% to 50% of the total mass of the formaldehyde-free adhesive.
[0075] In some embodiments, when mixing soy protein powder, crosslinking agent, and anti-mold particles with wood units, each component is directly stirred and mixed with the wood units, eliminating the need to pre-prepare an aqueous adhesive from the solid soy protein powder. Directly mixing the dry powder soy protein powder with the wood units eliminates the steps of preparing, storing, and coating the aqueous adhesive, reducing process complexity. Furthermore, it avoids the problems of high viscosity, short shelf life, and susceptibility to mold growth associated with aqueous adhesive systems, facilitating continuous production. During mixing, the anti-mold particles achieve uniform dispersion on the wet surface of the wood units through the hydrophilic functional groups of their shells, avoiding the agglomeration problem of hydrophobic anti-mold agents when added directly in powder form, ensuring uniform distribution of the hydrophobic anti-mold agent among the wood units. In other embodiments, soy protein powder, crosslinking agent, anti-mold particles, epoxidized natural rubber, and wood units can also be mixed to obtain a mixture.
[0076] In some embodiments, before preparing the artificial board, soy protein powder, crosslinking agent, anti-mildew particles, epoxidized natural rubber and alkali solution can be stored separately. When preparing the artificial board, the soy protein powder is first alkalized with alkali solution. The alkalized soy protein powder, crosslinking agent, anti-mildew particles and epoxidized natural rubber are then mixed to obtain a mixture.
[0077] Step S220 involves hot-pressing the mixture to allow the soybean protein powder to swell and activate in situ using the moisture in the wood units, and to crosslink and solidify with the crosslinking agent. During the hot-pressing process, the shell undergoes physical changes to release or expose the hydrophobic antifungal agent, and the hydrophilic functional groups react with the crosslinking agent to bond to the crosslinked and solidified network.
[0078] For example, a cross-linked curing network can characterize a three-dimensional polymer network structure formed by hot-pressing and curing soybean protein powder, cross-linking agent and reacting shell and / or other reactive components (such as epoxidized natural rubber), which is used to bond wood units together.
[0079] In some embodiments, hot pressing enables activation, antifungal agent release, sizing, and curing to be completed simultaneously in one step, integrating multiple traditional step-by-step processes into a single hot pressing step, simplifying the artificial board preparation process and improving production efficiency; in addition, the shell layer is chemically bonded to the cross-linked curing network, so that the shell layer of the antifungal particles will not remain as foreign matter in the cross-linked curing network and affect the bonding strength.
[0080] For example, the hydroxyl and / or carboxyl groups in the shell can undergo ring-opening reactions with the epoxy groups of a cross-linking agent (such as glycerol triglycidyl ether) to form covalent bonds, thus covalently bonding the shell to the cross-linked cured network. As another example, if the soy protein powder contains hydrophilic groups, these groups can undergo ring-opening reactions with the hydrophilic groups (such as hydroxyl, amino, and carboxyl groups) of the shell to form hydrogen bonds and other covalent bonds, thus hydrogen-bonding the shell to the cross-linked cured network. The shell is covalently bonded to the cross-linked cured network through chemical reactions, or through a combination of chemical reactions, covalent bonding, and hydrogen bonding, making the shell an organic component of the cross-linked cured network. This avoids the risk of the shell weakening the bonding interface strength as a non-reactive inclusion, maintaining the mechanical properties and water resistance of the cross-linked cured network while achieving anti-mildew function.
[0081] By directly mixing soy protein powder, crosslinking agent, and anti-mold granules with wood units, the step of pre-preparing water-based adhesive is eliminated, simplifying the process. During hot pressing, the soy protein powder swells and activates in situ using the moisture in the wood units, crosslinks and cures with the crosslinking agent, and the shell undergoes physical changes to release or expose the hydrophobic anti-mold agent. Furthermore, the hydrophilic functional groups of the shell react with the crosslinking agent and bond to the crosslinked curing network, achieving simultaneous activation, sizing, curing, and anti-mold agent release. This integrates adhesive curing and engineered wood panel preparation, reducing production costs and energy consumption. In addition, the core-shell structure of the anti-mold granules ensures controlled release of the hydrophobic anti-mold agent during hot pressing, guaranteeing the anti-mold effect.
[0082] In some embodiments, the wood unit includes at least one of the following: wood shavings, wood fibers, bamboo shavings, and bamboo fibers; and / or, the moisture content of the wood unit is greater than 10%.
[0083] In some embodiments, the wood unit may include wood shavings. In other embodiments, the wood unit may include wood fibers. Wood fibers are the basic unit in the preparation of fiberboard (such as medium-density fiberboard), and the selection of wood fibers makes the preparation of this engineered wood product suitable for fiberboard production. Furthermore, the wood unit may also include bamboo shavings or bamboo fibers. Bamboo grows rapidly and is highly renewable; using bamboo shavings as a wood unit expands the source of raw materials and helps reduce dependence on timber resources. Bamboo fibers have high mechanical strength, and engineered wood products made with bamboo fibers as the wood unit can achieve good mechanical properties while utilizing the renewable advantage of bamboo resources.
[0084] In some embodiments, the moisture content of the wood unit is greater than 10%. A moisture content greater than 10% ensures that the wood unit contains sufficient moisture to serve as a water source for the in-situ swelling and activation of the soy protein powder.
[0085] By limiting the sources of various feasible wood units, the preparation method of this engineered wood product can be flexibly adapted to different raw materials and end products (such as particleboard, fiberboard, etc.), thus broadening the applicability of the process. The limitation of a moisture content greater than 10% is a key prerequisite for ensuring that soy protein powder can utilize the moisture of the wood units themselves for in-situ swelling and activation. Under this moisture content condition, the activation process of soy protein powder can be driven without adding large amounts of water or pre-preparing a glue solution, simplifying the process and reducing drying energy consumption.
[0086] The preparation method of formaldehyde-free adhesive system and wood-based panels has been explained above. The following is a further explanation of the wood-based panel products prepared by this method.
[0087] In some embodiments, the engineered wood panel may specifically include: a plurality of wood units; and a cross-linked curing network cured between the wood units, the cross-linked curing network being formed by curing the above-described formaldehyde-free adhesive system after hot pressing.
[0088] Wood units can be, for example, wood shavings, wood fibers, bamboo shavings, or bamboo fibers. Multiple wood units constitute the skeletal structure of the engineered wood panel. They are interconnected under the adhesive action of a cross-linking and curing network to form an integral panel structure, providing the required mechanical load-bearing capacity. The cross-linking and curing network is cured between the wood units, gluing and fixing adjacent wood units together. The cross-linking and curing network is formed by hot-pressing and cross-linking the cross-linking agent in a formaldehyde-free adhesive system with the active groups of soy protein powder and the hydrophilic functional groups of the shell, resulting in a strong adhesive bond between the wood units and good water resistance. Because the formaldehyde-free adhesive system does not contain formaldehyde, the engineered wood panel prepared does not pose any environmental or health risks from the release of free formaldehyde.
[0089] In the cross-linked curing network, the shell of the anti-mold particles has been covalently bonded to the network through the reaction of hydrophilic functional groups with the cross-linking agent. The hydrophobic anti-mold agent is released or exposed during the hot-pressing process through physical changes in the shell. After being released during hot-pressing, the hydrophobic anti-mold agent is distributed throughout the cross-linked curing network, providing durable anti-mold protection for the engineered wood product. The shell, bonded to the cross-linked network, becomes an organic component of the network, avoiding the adverse effects of shell residues as foreign matter on the bonding strength, thus achieving a synergistic effect between anti-mold performance and bonding performance.
[0090] The present disclosure will be further explained below with reference to specific embodiments. It should be noted that the following embodiments are only used to explain the present disclosure and should not be construed as limiting the present disclosure.
[0091] Example 1 A formaldehyde-free adhesive system comprises soy protein powder, a crosslinking agent, anti-mold particles, and epoxidized natural rubber. The soy protein powder is defatted soy flour (protein content not less than 45 wt%), the crosslinking agent accounts for 7.5% of the total mass of the formaldehyde-free adhesive system, the anti-mold particles account for 6% of the total mass of the formaldehyde-free adhesive system, the epoxidized natural rubber accounts for 15% of the total mass of the formaldehyde-free adhesive system, and the remainder is defatted soy flour. The anti-mold particles have a particle size of 1 μm.
[0092] The crosslinking agent used is glycerol triglycidyl ether.
[0093] The anti-mildew granules have a core-shell structure. The granule body (or core) is glyceryl monolaurate, and the shell is a composite shell of carboxymethyl starch and polyvinyl alcohol. The preparation method of the anti-mildew granules is as follows: glyceryl monolaurate is heated to 70℃ to melt it. An aqueous solution containing carboxymethyl starch and polyvinyl alcohol (mass ratio of carboxymethyl starch:polyvinyl alcohol = 3:1) is added under stirring. The mixture is then emulsified at high speed to form an emulsion, followed by spray drying to obtain a dry powder. The resulting anti-mildew granules have a particle size of approximately 50 μm and a shell thickness of approximately 20 μm. The shell contains hydrophilic functional groups of hydroxyl and carboxyl groups.
[0094] The wood unit is poplar wood shavings with a moisture content of 12%.
[0095] The preparation method of engineered wood panels is as follows: Defatted soybean flour, glycerol triglycidyl ether, anti-mildew granules, and epoxidized natural rubber were directly mixed with poplar wood shavings in a mixer according to the above-mentioned mass ratio to obtain a mixture. After the mixture was laid out and shaped, it was hot-pressed for 5 minutes at a temperature of 200°C and a pressure of 5 MPa, and then cooled to room temperature to obtain the engineered wood panel.
[0096] During the hot-pressing process, the soy protein powder swells and activates in situ using the moisture from the wood shavings themselves; the shell of the anti-mold particles softens and partially ruptures under the action of heat and pressure, releasing or exposing monoglycerides of laurate in the core; the hydroxyl and carboxyl groups in the shell undergo a ring-opening reaction with glycerol triglycidyl ether and bond to the cross-linked and solidified network of soy protein; the epoxy groups of epoxidized natural rubber also participate in the cross-linking reaction, introducing flexible segments.
[0097] Example 2 The preparation methods of the formaldehyde-free adhesive system and the artificial board are basically the same as in Example 1, except that the mass of glycerol triglycidyl ether is 0.5% of the total mass of the formaldehyde-free adhesive system.
[0098] Example 3 The preparation methods of the formaldehyde-free adhesive system and the artificial board are basically the same as in Example 1, except that the mass of glycerol triglycidyl ether is 10% of the total mass of the formaldehyde-free adhesive system.
[0099] Example 4 The preparation methods of the formaldehyde-free adhesive system and the artificial board are basically the same as in Example 1, except that the mass of the anti-mildew particles is 2% of the total mass of the formaldehyde-free adhesive system.
[0100] Example 5 The preparation methods of the formaldehyde-free adhesive system and the artificial board are basically the same as in Example 1, except that the mass of the anti-mildew particles is 10% of the total mass of the formaldehyde-free adhesive system.
[0101] Example 6 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the particle size of the anti-mildew particles is 50nm.
[0102] Example 7 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the particle size of the anti-mildew particles is 100μm.
[0103] Example 8 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the thickness of the shell layer is 10 nm.
[0104] Example 9 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the thickness of the shell layer is 100 μm.
[0105] Example 10 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the shell is a composite shell of carboxymethyl cyclodextrin and oxidized starch.
[0106] Example 11 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the shell is a composite shell of carboxymethyl cyclodextrin and chitosan.
[0107] Example 12 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the shell is a composite shell of carboxymethyl cyclodextrin and quaternized chitosan.
[0108] Example 13 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the hydrophobic mildew inhibitor is a complex of glyceryl monolaurate and glycerol triglycidyl ether.
[0109] Example 14 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the hydrophobic mildew inhibitor is a complex of glyceryl monolaurate and epoxidized natural rubber.
[0110] Example 15 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the hydrophobic mildew inhibitor is a complex of glyceryl monolaurate, glycerol triglycidyl ether and epoxidized natural rubber.
[0111] Comparative Example 1 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that no anti-mildew particles are added.
[0112] Comparative Example 2 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the anti-mildew particles are replaced with an equal mass of uncoated glyceryl monolaurate powder (i.e., without a shell).
[0113] Comparative Example 3 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that glycerol triglycidyl ether is not added.
[0114] Comparative Example 4 The preparation methods of the formaldehyde-free adhesive system and the artificial board are basically the same as in Example 1, except that the mass of the anti-mildew particles is 12% of the total mass of the formaldehyde-free adhesive system (exceeding the upper limit of 10%).
[0115] Comparative Example 5 The preparation method of the formaldehyde-free adhesive system and the artificial board is basically the same as in Example 1, except that the particle size of the anti-mildew particles is 200μm (exceeding the upper limit of 100μm).
[0116] The internal bond strength, boiling water internal bond strength, and mildew resistance rating of the engineered wood panels prepared in each embodiment and comparative example are shown in Table 1 below. The internal bond strength and boiling water internal bond strength were tested according to GB / T 4897-2015, and the mildew resistance rating was tested according to GB / T 18261-2013. The testing period was 4 weeks. The mildew resistance rating was divided according to the mildew area: Grade 0 was no mildew, Grade 1 was mildew area ≤25%, Grade 2 was mildew area 25%~50%, Grade 3 was mildew area 50%~75%, and Grade 4 was mildew area >75%.
[0117] Table 1 In Table 1, CMS / PVA represents carboxymethyl starch / polyvinyl alcohol; CMCD / OS represents carboxymethyl cyclodextrin / oxidized starch; CMCD / CS represents carboxymethyl cyclodextrin / chitosan; and CMCD / QCS represents carboxymethyl cyclodextrin / quaternized chitosan.
[0118] As shown in Table 1, Examples 1-15 all exhibited high internal bond strength and water-resistant internal bond strength, achieving a mildew resistance rating of 0 or 1. This indicates that the synergistic effect of the core-shell structured mildew-resistant particles and the crosslinking agent effectively prevented mildew while avoiding the weakening of the crosslinking and curing network. Examples 4 and 5 and Comparative Example 4 show that when the amount of mildew-resistant particles is between 2% and 10%, the mildew resistance rating can reach 1 or better, and the internal bond strength remains above 1.35 MPa. When the amount increases to 12%, the bonding strength decreases, indicating that excessive mildew-resistant particles affect the continuity of the bonding interface.
[0119] Examples 6 and 7 and Comparative Example 5 show that the anti-mold particles with a particle size in the range of 50 nm to 100 μm have good dispersibility and release effect, with an anti-mold grade of 0 and an internal binding strength of more than 1.23 MPa; however, when the particle size increases to 200 μm, the shell opening is delayed and the dispersion is uneven, the anti-mold effect decreases, and the internal binding strength also decreases.
[0120] Examples 8 and 9 demonstrate the effect of shell thickness range; within the range of 12 nm to 100 μm, the antifungal particles reliably open and release the hydrophobic antifungal agent, and the shell participates in crosslinking without significantly adversely affecting the adhesive strength. Examples 10-12 show that different shells containing hydrophilic functional groups can react with glycerol triglycidyl ether to become part of the crosslinked and cured network. Examples 13-15 use composite antifungal particle bodies, and the internal bond strength and boiling water bond strength are comparable to or slightly improved compared to Example 1, indicating that the composite antifungal particle body can also be used in the formaldehyde-free adhesive system of this disclosure.
[0121] Comparative Example 1, lacking anti-mold particles, had a mold resistance level of 4 and suffered severe mold growth, indicating that anti-mold particles are a necessary factor for achieving mold prevention. Comparative Example 2 directly used glyceryl monolaurate powder; due to the agglomeration of hydrophobic glyceryl monolaurate in wet wood shavings, its dispersibility was poor, resulting in a mold resistance level of 2. Furthermore, its inert nature reduced the bond strength. Comparative Example 3, without the addition of a crosslinking agent, showed a sharp drop in internal bond strength to 0.15 MPa after boiling, demonstrating that a crosslinking agent is crucial for constructing a crosslinked curing network.
[0122] Therefore, when the shell of the anti-mold particles contains hydrophilic functional groups such as hydroxyl and / or carboxyl groups, it can be uniformly dispersed in the water-containing wood units. During the hot pressing process, it releases or exposes the hydrophobic anti-mold agent in a timely manner through physical changes such as softening, melting, cracking or shrinkage. The shell reacts with the crosslinking agent and bonds to the crosslinking and curing network, thereby solving the contradiction between the dispersibility of the anti-mold agent and the bonding strength.
[0123] The basic principles of this disclosure have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in this disclosure are merely examples and not limitations, and should not be considered as essential features of each embodiment of this disclosure. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the scope of this disclosure to the necessity of employing the aforementioned specific details for implementation.
[0124] The block diagrams of devices, apparatuses, devices, and systems disclosed herein are merely illustrative examples and are not intended to require or imply that they must be connected, arranged, or configured in the manner shown in the block diagrams. As those skilled in the art will recognize, these devices, apparatuses, devices, and systems can be connected, arranged, and configured in any manner. Words such as “comprising,” “including,” “having,” etc., are open-ended terms meaning “including but not limited to,” and are used interchangeably with them. The terms “or” and “and” as used herein refer to the terms “and / or,” and are used interchangeably with them unless the context clearly indicates otherwise. The term “such as” as used herein refers to the phrase “such as but not limited to,” and is used interchangeably with it.
[0125] It should also be noted that in the apparatus, devices, and methods of this disclosure, the components or steps can be disassembled and / or recombined. These disassemblies and / or recombinations should be considered as equivalent solutions to this disclosure.
[0126] The above description of the disclosed aspects is provided to enable any person skilled in the art to make or use this disclosure. Various modifications to these aspects will be readily apparent to those skilled in the art, and the general principles defined herein may be applied to other aspects without departing from the scope of this disclosure. Therefore, this disclosure is not intended to be limited to the aspects shown herein, but rather to be carried out within the widest scope consistent with the principles and novel features disclosed herein.
[0127] The above description has been given for purposes of illustration and description. Furthermore, this description is not intended to limit the embodiments of this disclosure to the forms disclosed herein. Although numerous exemplary aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, alterations, additions, and sub-combinations thereof.
[0128] The specific embodiments described above do not constitute a limitation on the scope of protection of this invention. Those skilled in the art should understand that various modifications, combinations, sub-combinations, and substitutions can be made according to design requirements and other factors. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A formaldehyde-free adhesive system, characterized in that, include: Soy-based protein powder; Crosslinking agent; as well as Anti-mold granules, comprising an anti-mold granule body and a shell layer, wherein the shell layer covers at least a portion of the anti-mold granule body; the anti-mold granule body comprises a hydrophobic anti-mold agent; the shell layer comprises hydrophilic functional groups, wherein the shell layer is configured to undergo a physical change during hot pressing to release or expose the hydrophobic anti-mold agent, and the hydrophilic functional groups are capable of reacting with the crosslinking agent; wherein the soy protein powder is configured to utilize the moisture of the lignin units for in-situ swelling and activation.
2. The formaldehyde-free adhesive system according to claim 1, characterized in that, The crosslinking agent is present in an amount of 0.5% to 10% of the total mass of the formaldehyde-free adhesive system, and / or, The mass of the anti-mildew particles is 2% to 10% of the total mass of the formaldehyde-free adhesive system, and / or, The particle size of the anti-mildew particles is 50 nanometers to 100 micrometers.
3. The formaldehyde-free adhesive system according to claim 1, characterized in that, It also includes epoxidized natural rubber, the mass of which is 5% to 30% of the total mass of the formaldehyde-free adhesive system.
4. The formaldehyde-free adhesive system according to any one of claims 1 to 3, characterized in that, The shell is any one of the following: a composite shell of carboxymethyl starch and polyvinyl alcohol, a composite shell of carboxymethyl cyclodextrin and oxidized starch, a composite shell of carboxymethyl cyclodextrin and chitosan, or a composite shell of carboxymethyl cyclodextrin and quaternized chitosan.
5. The formaldehyde-free adhesive system according to claim 4, characterized in that, The hydrophilic functional groups of the shell include at least one of the following: hydroxyl, carboxyl, carboxylate, hydroxypropyl, and amino.
6. The formaldehyde-free adhesive system according to claim 1, characterized in that, The anti-mildew granules are selected from: glyceryl monolaurate; or a complex of glyceryl monolaurate, glycerol triglycidyl ether, and / or epoxidized natural rubber.
7. The formaldehyde-free adhesive system according to any one of claims 1 to 3, characterized in that, The thickness of the shell is 10 nanometers to 100 micrometers, and / or, The crosslinking agent includes a polyepoxy crosslinking agent, which includes glycerol triglycidyl ether, and / or... The physical changes include at least one of the following: softening, melting, cracking, and shrinkage.
8. A method for preparing a type of engineered wood panel, characterized in that, include: Soy protein powder, a crosslinking agent, and anti-mold granules are mixed with wood units to obtain a mixture. The anti-mold granules include an anti-mold granule body and a shell layer. The shell layer covers at least a portion of the anti-mold granule body. The anti-mold granule body includes a hydrophobic anti-mold agent. The shell layer includes hydrophilic functional groups. The shell layer is configured to undergo a physical change during hot pressing to release or expose the hydrophobic anti-mold agent, and the hydrophilic functional groups are capable of reacting with the crosslinking agent. The mixture is subjected to hot pressing, which causes the soybean protein powder to swell and activate in situ using the moisture in the wood units, and to crosslink and cure with the crosslinking agent. During the hot pressing process, the shell undergoes physical changes to release or expose the hydrophobic antifungal agent, and the hydrophilic functional groups react with the crosslinking agent to bond to the crosslinked and cured network.
9. The method according to claim 8, characterized in that, The wood unit includes at least one of the following: wood shavings, wood fibers, bamboo shavings, and bamboo fibers; and / or, The moisture content of the wood unit is greater than 10%.
10. A type of engineered wood panel, characterized in that, include: Multiple wooden units; And a cross-linked curing network solidified between the wood units, the cross-linked curing network being formed by hot pressing and curing of the formaldehyde-free adhesive system according to any one of claims 1 to 7.